Configural asymmetries: an effect of context and object based processes - Edler, Joshua R., author; Monnier, Patrick, advisor; Draper, Bruce, committee member; Clegg, Benjamin, committee member (Colorado State University. Libraries, 2010)
Configural asymmetries refer to differences in visual search performance in which displays composed of objects requiring left/right judgments, are slower to process and incur more errors than displays composed of objects requiring up/down judgments. Two accounts of the effect have emerged in the literature. The Object Region Account, an object-based explanation, posits configural asymmetries are driven by differences in processing the up/down versus left/right regions of an individual object, with left/right regions being less finely processed. The Inter-item Symmetry account, a context-based explanation, posits configural asymmetries are due to mirror symmetry relationships shared between multiple elements in the search display. Specifically, objects sharing vertical mirror symmetry are perceived as more similar and therefore harder to process than objects sharing horizontal mirror symmetry. This study attempted to test and separate these two accounts. Measurements demonstrated that mirror symmetry relationships alone between target and distractors indeed produced an asymmetry in search performance--horizontal mirror symmetry was easier to search through than vertical mirror symmetry. Albeit the magnitude of the effect produced solely by mirror symmetry was noticeably smaller than the effect obtained when objects required left/right versus up/down comparisons (e.g., Monnier, Atarha, Edler, & Birks, 2010; Van Zoest, Giesbrecht, Enns, Kingstone, 2006). Furthermore, when mirror symmetry was held between distractors the reverse effect was found - vertical mirror symmetry was easier to search through than horizontal mirror symmetry. These measurements support configural asymmetries are best understood as an interaction of both object-based and context-based processes and provide support that mirror symmetry is a dimension by which the visual system groups objects.
Covers not scanned.
Keywords: Visual perception; Mirror symmetry